Influence law of temperature profile for horizontal wells in tight oil reservoirs - LUO Hongwen, ZHANG Qin, LI Haitao, XIANG Yuxing, LI Ying, PANG Wei, LIU Chang, YU Hao, WANG Yaning (Youqicang pingjia yu kaifa, 2023)
The challenge of reliably predicting temperature profiles in horizontal wells in tight oil reservoirs, coupled with an incomplete understanding of the factors influencing these profiles, has hindered the quantitative interpretation of tight oil horizontal well production using distributed optical fiber technology. To address this issue, a comprehensive model has been developed to estimate temperature profiles in horizontal wells in tight oil reservoirs, accounting for various microthermal effects. The temperature profiles of horizontal wells in tight oil reservoir under different single factors were simulated and analyzed. Then, through orthogonal experiment analysis, it demonstrates that the sensitivity of different factors from strong to weak is production rate, fracture half-length, reservoir permeability, wellbore diameter, horizontal inclination angle, fracture conductivity, and total reservoir thermal conductivity（Q>xf>K>D>θ>FCD>Kt）. It is worth noting that fracture half-length and formation permeability emerged as the primary factors influencing the temperature profile of horizontal wells in tight oil reservoirs. The research results provide available basic models and theoretical support for quantitative interpretation of production profile and artificial fracture parameters for horizontal wells in tight oil reservoir.